Validation of Worry Behaviors Inventory (WBI) among Normal Population - Amiri, Sohrab; Farzalizadeh, Vida; Jamali, Yosef; Babaei, Karim (International Journal of Applied Behavioral Sciences, 2017)
Objective: This study aimed to evaluate the psychometric properties of Worry Behaviors Inventory (WBI) in normal population.Method: For this purpose, 286 participations (first study) and 40 participations (Second study) were selected in 2017. Then Worry Behaviors Inventory (WBI), Patient Health Questionnaire-9, WHODAS-II, HAQ, PHQ-15 and CABAH were distributed among them to respond. After collecting data, the reliability of the Inventory was assessed by using SPSS-22 and Lisrel 8.8, Cronbach's alpha, retest and split-half coefficient, then the Construct validity with other questionnaires to determine the psychometric properties of the Worry Behaviors Inventory (WBI). The Factor structure was assessed by confirmatory factor analysis.Results: The results of the factor analysis indicated that WBI has two factors and checking the reliability of the Inventory using Cronbach's alpha, test-retest and split-half coefficient reflects the stability of the scale, the Construct validity of the WBI with other questionnaires showed desirable discriminant and convergence validity.Conclusions: Overall, the findings indicated that WBI has good psychometric properties in normal population, and the tool can be used in studies in somatoform disorders. However, it seems that Worry Behaviors is the fundamental structure of somatoform disorders.